Surgically-assisted rapid maxillary expansion (SARME): indications, planning and treatment of severe maxillary deficiency in an adult patient - Lívia Loriato; Carlos Eduardo Ferreira (Dental Press Editora, 2020)
ABSTRACT Introduction: Maxillary deficiency, also called transverse deficiency of the maxilla, may be associated with posterior crossbite, as well as with other functional changes, particularly respiratory. In adult patients, because of bone maturation and the midpalatal suture fusion, rapid maxillary expansion has to be combined with a previous surgical procedure to release the areas of resistance of the maxilla. This procedure is known as surgically-assisted rapid maxillary expansion (SARME). Objective: This study discusses the indications, characteristics and effects of SARME, and presents a clinical case of transverse and sagittal skeletal maxillary discrepancy treated using SARME and orthodontic camouflage.